Students’ Perspectives on AI Integration in Classroom-Based Sustainability Education in Malaysia - Rafidah Abd Karim; Nurul Farhani Che Ghani; Farahidatul Akmar Awaludin; Azurawati Zaidi; Nor Najihah Norafand (European Scientific Journal, ESJ, 2026)
Sustainability education aims to enhance environmental knowledge and foster civic engagement through effective pedagogical strategies. The integration of Artificial Intelligence (AI) into education offers a transformative opportunity to support students in understanding sustainability-related opportunities and challenges. By cultivating a global perspective, optimizing resource allocation, and personalising learning experiences, AI-driven approaches can significantly enrich sustainability education and better prepare students for a sustainable future. AI applications in education encompass learning enhancement, individualized instruction, and administrative efficiency, ultimately contributing to more effective teaching and learning processes. This study examines students’ perceptions of AI integration in the classroom in relation to sustainability education within Malaysian higher education institutions. A quantitative case study was conducted with 175 participants from a selected public university in Malaysia. Data were collected through online questionnaires, and the responses were analyzed using SPSS version 27. The findings provide valuable insights for academicians, researchers, universities, and policymakers in formulating strategies to equip future generations with the competencies required to address the complex sustainability challenges of the 21st century and beyond.